Pengaruh MNC terhadap Ekonomi Politik Host Country: Studi Kasus KFC di Negara Jepang - Nurhakim, Kasta Alfian; Wijayati, Hasna (Penerbit Goodwood, 2024)
Purpose: This study aims to analyze how KFC, as a multinational corporation (MNC), influences the political economy of Japan as a host country. Methods: The study employs a qualitative descriptive research method, utilizing a literature review approach. Data analysis is conducted using Miles and Huberman's qualitative analysis framework, which includes data reduction, data presentation, and drawing conclusions/verification. Results: The study finds that MNCs can significantly impact the political economy of host countries. In the case of KFC in Japan, the influence is evident through economic growth driven by foreign direct investment, which creates jobs and boosts local income. Additionally, KFC introduces advanced management, operational, and marketing technologies, enhancing efficiency and productivity in the local fast food industry. Cooperation with local suppliers also stimulates growth in the agricultural sector and related industries in Japan. Limitations: This study is limited to a case study of a single MNC in one host country, which may restrict the generalizability of the findings to other political economy contexts. Contribution: This research contributes to the field of international relations, particularly within the concentration of global political economy studies, by providing insights into the impact of MNCs on the political and economic dynamics of host countries.